2022
DOI: 10.1002/smll.202205323
|View full text |Cite
|
Sign up to set email alerts
|

A Tin Oxide‐Coated Copper Foam Hybridized with a Gas Diffusion Electrode for Efficient CO2 Reduction to Formate with a Current Density Exceeding 1 A cm−2

Abstract: The electrochemical CO2 reduction reaction (CO2RR) is a promising strategy for closing the carbon cycle. Increasing the current density (  J) for CO2RR products is a critical requirement for the social implementation of this technology. Herein, nanoscale tin–oxide‐modified copper–oxide foam is hybridized with a carbon‐based gas‐diffusion electrode (GDE). Using the resultant electrode, the Jformate is increased to −1152 mA cm−2 at −1.2 V versus RHE in 1 m KOH, which is the highest value for CO2‐to‐formate elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The formate concentration value could reach 27 g L −1 (0.6 M) with a FE of 44.9% at 300 mA cm −2 . Besides, Liu et al [126] combined nano SnO-modified CuO foam with a carbon-based GDE to convert CO 2 into formate. The results showed ultrahigh rate formate production.…”
Section: Gas Diffusion Electrodes (Gdes)mentioning
confidence: 99%
See 2 more Smart Citations
“…The formate concentration value could reach 27 g L −1 (0.6 M) with a FE of 44.9% at 300 mA cm −2 . Besides, Liu et al [126] combined nano SnO-modified CuO foam with a carbon-based GDE to convert CO 2 into formate. The results showed ultrahigh rate formate production.…”
Section: Gas Diffusion Electrodes (Gdes)mentioning
confidence: 99%
“…As the homogeneously modified Sn atoms suppressed the generation of H2 and hydrophobic carbon nanoparticles on the GDE penetrated the microporous structure of the Cu foam increased the reaction area in the three-phase interface. [126] Recently, an ultrahigh current density of 2.0 A cm −2 with a formate FE of 93% at −0.95 V versus RHE has been achieved by Lin et al [127] They designed a Bi 2 S 3 -derived electrocatalyst via a solvothermal method loaded on carbon paper as GDE in a flow cell for CO 2 RR. The stability of formatting formate could maintain 100 h with an FE > 90% at an industrial-relevant current density of 250 mA cm −2 .…”
Section: Gas Diffusion Electrodes (Gdes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the other supports, such as the metal foams and frameworks, [ 34,36–39 ] carbon supports are smaller and more adaptable. More importantly, numerous studies have found that the outstanding performance of carbon‐supported catalysts probably arises from the interface effect between carbon supports and catalyst particles.…”
Section: Why Choose Biomass For Electrocatalysts?mentioning
confidence: 99%
“…[5][6][7][8] Hereby, it is urgent to develop more high performance electrocatalyst to boost the CO 2 -to-formate reduction. Heretofore, metal-based catalysts (such as Bi, [9][10][11][12] Sn, [13][14][15] In, [16][17][18] Pb, [19,20] and Pd, [21][22][23] ) present excellent formate selectivity in the eCO 2 RR process. Among them, Bi-based catalysts present the strong OCHO* stability and large hydrogen evolution overpotential, which make them be one of most promising electrocatalysts with superior performance.…”
Section: Introductionmentioning
confidence: 99%